The ideology of the International criminal court: human-centrism, structural tensions, and transnational challenges - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (Elsevier, 2026)
The International Criminal Court (ICC) was conceived as a normative and institutional rupture with the sovereignty-centred tradition of international law: a permanent court grounded not in the will of states but in the inherent dignity of individuals and the imperative to protect victims of the most serious crimes. This article offers a comprehensive ideological analysis of the ICC - its foundational human-centred commitment, the structural tensions that beset its operation, and the transnational challenges that test the adequacy of its normative architecture. Drawing on the concept of criminal-law ideology developed in Ukrainian legal scholarship, and engaging with the Court's own jurisprudence, the Rome Statute's drafting history, and the broader framework of international, European and transnational criminal law, the article argues that the ICC embodies four interrelated ideological dimensions: (1) human-centrism as a legitimating axis that simultaneously grounds and overburdens the Court's claims; (2) complementarity as an ideological battleground where competing conceptions of justice, sovereignty and good faith collide; (3) contextual thresholds that create normative vacuums at the interface with transnational criminal law, excluding from the Court's reach forms of harm that are morally comparable to its core crimes; and (4) an individualistic responsibility paradigm that is structurally blind to the corporate, network and algorithmic actors that increasingly determine the conditions under which mass harm occurs. Each dimension is examined in depth, and a series of normative proposals is developed for re-articulating the Court's ideology in response to twenty-first century challenges. Міжнародний кримінальний суд (МКС) був задуманий як нормативний та інституційний розрив із традицією міжнародного права, орієнтованою на суверенітет: постійний суд, заснований не на волі держав, а на притаманній гідності окремих осіб та імперативі захисту жертв найтяжчих злочинів. Ця стаття пропонує комплексний ідеологічний аналіз МКС – його основоположного, людиноцентричного зобов'язання, структурних напружень, що перешкоджають його функціонуванню, та транснаціональних викликів, які перевіряють адекватність його нормативної архітектури. Спираючись на концепцію кримінально-правової ідеології, розроблену в українській правовій науці, та взаємодіючи з власною юриспруденцією Суду, історією розробки Римського статуту та ширшими рамками міжнародного, європейського та транснаціонального кримінального права, у статті стверджується, що МКС втілює чотири взаємопов'язані ідеологічні виміри: (1) людиноцентризм як легітимізуюча вісь, яка одночасно обґрунтовує та перевантажує вимоги Суду; (2) взаємодоповнюваність як ідеологічне поле битви, де стикаються конкуруючі концепції справедливості, суверенітету та добросовісності; (3) контекстуальні пороги, що створюють нормативний вакуум на межі з транснаціональним кримінальним правом, виключаючи з досяжності Суду форми шкоди, які морально порівнянні з його основними злочинами; та (4) парадигму індивідуалістичної відповідальності, яка структурно сліпа до корпоративних, мережевих та алгоритмічних акторів, які все більше визначають умови, за яких відбувається масова шкода. Кожен вимір детально досліджується, і розроблено серію нормативних пропозицій для переосмислення ідеології Суду у відповідь на виклики ХХІ століття.
Tuliakov V. O. The ideology of the International criminal court: human-centrism, structural tensions, and transnational challenges. SSRN : website. P. 22. URL: https://papers.ssrn.com/sol3/papers.cfm?abstract_id=6558018 ; http://dx.doi.org/10.2139/ssrn.6558018 ; https://hdl.handle.net/11300/32647. Publication date: 11.04.2026
Keywords: International Criminal Court; criminal-law ideology; human-centrism; complementarity; Rome Statute; contextual thresholds; transnational criminal law; European criminal law; corporate accountability; algorithmic governance; organisational fault; normative vacuum; penal populism; Ukrainian criminal-law doctrine; Міжнародний кримінальний суд; ідеологія кримінального права; людиноцентризм; взаємодоповнюваність; Римський статут; контекстуальні пороги; транснаціональне кримінальне право; Європейське кримінальне право; корпоративна відповідальність; алгоритмічне управління; Організаційна помилка; нормативний вакуум; кримінальний популізм; українська кримінально-правова доктрина